REKOMENDASI JURUSAN TERBAIK SEKOLAH MENENGAH KEJURUAN (SMK) KOTA CILEGON DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Haris Triono Sigit; Sulistiyono; Suherman (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This research will help students in choosing majors at SMK Cilegon City, namely by creating a website application by providing choices of majors criteria that have been determined by the Admin. The method used is Simple Additive Weighting (SAW). The advantage of this SAW method lies in its ability to make a more precise assessment because it is based on the value of the criteria and the weight of the level of importance required. The SAW method can also select the best alternative from a number of available alternatives, then a ranking process is carried out in which the total weight values ​​of all criteria are added up after determining the weight value of each criterion. The way this method works is to search for majors based on the selected criteria so that it will display in detail about the majors.